Standardisation of Nursery Technique (use of Different Germination Media and Watering Methods) of Anthocephalus chlnensis - Beniwal, B. S.; Dhawan, V. K. (Indian Forester, 1991)
The paper presents a study on the germination behaviour of pulped as well as depulped seeds of Anthocephalus chinensis and the effect of different soil media and watering methods on the germination and growth of seedlings. The results indicate that sowing of pulped seeds give poor germination compared to depulped seeds. Further, use of soil media and watering with the help of Can or fine Sprayer gives maximum germination.